Competence, Innovative Work Behavior, and Work Engagement: A Comparison of Generation X and Millennials - Mafizatun Nurhayati; Nia Kusumawardani; Asep Rokhyadi Permana Saputra; Awan Santosa (Jurnal Organisasi dan Manajemen, 2023)
Purpose – This study aimed to analyze the effect of competence on innovative work behavior through work engagement by comparing Generation X and millennials during the Covid-19 pandemic.  Methodology – It was conducted on 114 employees of the Ministry of Education, Culture, Research, and Technology,  at High School Directorate. The data were further analyzed using Structural Equation Model-Partial Least Square (SEM-PLS). Findings –The results proved that competence positively affects work engagement and innovative behavior. Work engagement also mediates the effect of competence on innovative work behavior. Moreover, the effect on Generation X is higher than on Millennials. This is because Generation X dominates important positions and has a greater responsibility in public organizations. They are also more loyal and have high intrinsic motivation with high competence. Therefore, Generation X has higher work engagement and better innovative behavior due to more responsibilities. Originality – The model built in this study uses a multi-group analysis that compares Millennials and Generation X employees. This analysis is interesting because it is relatively rare to find similar analyzes in previous studies, and it is useful to find out whether managing employees from different generations requires different policies.